Gene editing with ‘pencil’ rather than ‘scissors’ in human pluripotent stem cells - Ju-Chan Park; Mihn Jeong Park; Seung-Yeon Lee; Dayeon Kim; Keun-Tae Kim; Hyeon-Ki Jang; Hyuk-Jin Cha (Stem Cell Research & Therapy, 2023)
Abstract Owing to the advances in genome editing technologies, research on human pluripotent stem cells (hPSCs) have recently undergone breakthroughs that enable precise alteration of desired nucleotide bases in hPSCs for the creation of isogenic disease models or for autologous ex vivo cell therapy. As pathogenic variants largely consist of point mutations, precise substitution of mutated bases in hPSCs allows researchers study disease mechanisms with “disease-in-a-dish” and provide functionally repaired cells to patients for cell therapy. To this end, in addition to utilizing the conventional homologous directed repair system in the knock-in strategy based on endonuclease activity of Cas9 (i.e., ‘scissors’ like gene editing), diverse toolkits for editing the desirable bases (i.e., ‘pencils’ like gene editing) that avoid the accidental insertion and deletion (indel) mutations as well as large harmful deletions have been developed. In this review, we summarize the recent progress in genome editing methodologies and employment of hPSCs for future translational applications.